A comparative review of Nettle and Ramie fiber and their use in biocomposites, particularly with a PLA matrix. Issue 14 (28th October 2022) - Bogard, Fabien; Bach, Thierry; Abbes, Boussad; Bliard, Christophe; Maalouf, Chadi; Bogard, Virginie; Beaumont, Fabien; Polidori, Guillaume
ABSTRACT: Current environmental concerns are increasingly forcing manufacturers to reduce the use of petroleum derivatives in order to reduce their carbon footprint. The use of new plant-based materials is therefore an interesting alternative to plastics. A certain number of plant fibers have been rediscovered for use in the form of agro-composites; Nettle fiber is one of them. The objective of this review is thus to take stock of current knowledge on the European Nettle fiber (Urtica Dioica) and its asian version (Boehmeria nivea, or Ramie), which are too often confused. This "weed, " which has been used since antiquity, is coming back into fashion thanks to the highlighting of some of its properties but also to its simplicity of cultivation. The association PLA/Nettle, lending itself perfectly to this concept of modern ecological material 100% biodegradable, is also highlighted in this work where the intrinsic qualities of each component are detailed based on the promising uses of this agro-composite mentioned in the literature or the automotive industry.